(untitled) (Research, Society and Development, 2018)
The article aims to investigate ways of promoting, through integrated and transdisciplinary practices, reading and writing skills of the academic field of the future bachelor in Law. To do so, we proposed an action research that allowed us, from procedures involving observation, interviews with focus group and questionnaire, to draw up a work agenda in order to change our form of classroom literacy. The dialogue among the professors of the Law course was also essential, as it allowed for interdisciplinary and multidisciplinary practices that would lead the academics to work in ways of reading and academic textual production that were effectively reflective, meaningful and collectivized. Thus, the activities developed by the students allowed to reveal to what extent a process and interdisciplinary work assists in the expansion of discursive-textual capacities, as well as the processes of learning, under a social and interactionist perspective, can allow a critical and authorial growth of the academic.